Folk Spiritism: Between Communication with the Dead and Heavenly Forces - Radulović, Nemanja (Religions, 2024)
Examples of how Spiritism merged with local beliefs have been the subject of research in religious studies, ethnology, and folkloristics. Serbian Spiritism can also be viewed as such, but its history is an under-researched topic. We examine the syncretic product we will call ‘folk Spiritism’, being different from the ‘high Spiritism’ of elite and middle-class intellectuals. Folk Spiritism was part of a grassroots movement for Church reform in the first half of the 20th century. The difference between folk and high Spiritism is also confirmed in the emic perspective. Based on a closer reading of its texts, we can discern a better image of the dead and communication with them in the practice of folk Spiritism. We conclude that the difference between the traditional and Spiritist image of the dead is that the former causes fear, while the later brings comfort; folk Spiritism gave preference to communication with heavenly forces (God, Christ, Holy Mother, angels, saints) while retaining the traditional view of the dead.